2021
DOI: 10.12788/jhm.3538
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Stewardship in the Transition From Intravenous to Enteral Antibiotics in Hospitalized Pediatric Patients

Abstract: BACKGROUND/OBJECTIVE: Pediatric patients hospitalized with bacterial infections often receive intravenous (IV) antibiotics. Early transition to enteral antibiotics can reduce hospital duration, cost, and complications. We aimed to identify opportunities to transition from IV to enteral antibiotics, describe variation of transition among hospitals, and evaluate feasibility of novel stewardship metrics. METHODS: This multisite retrospective cohort study used the Pediatric Health Information System to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The marked reduction in PICC placement should be celebrated but not met with complacency; current data continue to reveal wide variation in care patterns and opportunities for care improvement among children with osteomyelitis. 9,27 The rapid practice change observed in this study emphasizes the importance of longitudinal measurement of low-value services on a population basis. Regular measurement is needed to establish improvement targets and prioritize deimplementation initiatives.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The marked reduction in PICC placement should be celebrated but not met with complacency; current data continue to reveal wide variation in care patterns and opportunities for care improvement among children with osteomyelitis. 9,27 The rapid practice change observed in this study emphasizes the importance of longitudinal measurement of low-value services on a population basis. Regular measurement is needed to establish improvement targets and prioritize deimplementation initiatives.…”
mentioning
confidence: 87%
“…"Opportunity days," defined as those during which patients received parenteral antibiotics and at least 1 enteral nonantibiotic medication (supporting the ability to tolerate oral medications), accounted for 69% of osteomyelitis patient days. 27 Although clinical improvement and downtrending inflammatory markers typically guide the transition to oral antibiotics, approaches to this process remain variable. 5,9,27 Continued assessment of the optimal duration of intravenous therapy may identify opportunities to further reduce LOS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, prescribers should apply a structured approach, such as the “Four Moments of Antibiotic Decision Making,” on a daily basis for every hospitalized child receiving antibiotics to prompt timely decisions about discontinuing IV therapy, narrowing IV therapy, or transitioning from IV to oral antibiotic therapy 3 . We applaud Cotter et al for shedding light on an area in need of standardization of care, which could optimize patient outcomes and minimize harm for a large number of children 1 . The “percent opportunity” to switch from IV to oral antibiotic therapy is a promising antibiotic stewardship metric, and its association with clinical outcomes merits further investigation.…”
mentioning
confidence: 95%
“…In this issue of the Journal of Hospital Medicine, Cotter et al used an administrative database to investigate opportunities to transition from IV to oral antibiotics for patients across multiple pediatric hospitals. 1 Their novel metric, "percent opportunity," represents the percent of days that there was the opportunity to transition from IV to oral antibiotics. They found that over 50% of the time, IV antibiotics could have been switched to equivalent oral agents.…”
mentioning
confidence: 99%